Perencanaan dan Studi Kelayakan Pembangunan Perumahan di Desa Ngaru-Aru, Kecamatan Banyudono, Kabupaten Boyolali - Faizin, Bustanul, Budi Priyanto, S.T., M.T (2016)
This research aims to know the: (1) the amount of the need of the expected community residential homes, particularly in the village of Ngaru-aru, Kecamatan Banyudono, Boyolali Regency; (2) total investment analysis of the planning of residential development in the village of Ngaru-aru, Kecamatan Banyudono, Boyolali Regency; (3) investment plan worth or whether residential development in the village of Ngaru-aru, Kecamatan Banyudono, Boyolali Regency. The methods used in this study are descriptive and qualitative method conducted research using sampling techniques Slovin. There are two data analysis techniques, namely the analysis of the results of the test questionnaires and analysis of descriptive. The analysis of the results of the test questionnaires conducted statistical tests with the techniques of analysis of variance (anava) one line. Descriptive analysis using techniques that Miles and Huberman that includes: (1) plan drawings and cost budget; (2) analyze the feasibility by calculating the investment with a long Payback Period (PP), Return On Investment (ROI), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (IP), Benefit Cost Ratio (BCR). The result of the calculation of the budget plan total cost of the project amounted to Rp 9,909,401,237.98 and the estimated total income of 11,654,444,163 with 2-year investment plan of the age and interest of 10%. Residential development in the village investment Ngaru-aru, Kecamatan Banyudono, Boyolali Regency worthy, because NPV = Rp 1,282,526,731.95 > 0, IRR = 21.71% > 10%, IP = BCR = 1.091 > 1 and ROI = 54.06 >% 10%